Nichts ist vorbei, alles kommt wieder - Skapin, Anja (Vestnik za tuje jezike, 2012)
German Romanticism and its rich tradition remain deeply rooted to this day. Despite stereotypical linking of German culture with reason, the essence of German literary (and as well philosophical) ideology is nevertheless the dark side of human nature and all the raging emotions that comprise it. Social crisis, which is reflected as well, and primarily, in literature as a subtle and refined indicator of social conditions, is dealt with by revival of traditional narrative forms, particularly coming-of-age story (Ger. Bildungsroman) with its subgenre artist novel (Ger. Künstlerroman). Man is doomed to eternal suffering and longing (Schopenhauer) and the human history to eternal recurrence of the same forms and ideas (Nietzsche). Consequently, one cannot ignore the fact that the literary movement surging to the forefront of German literary production time and again is precisely the one that revealed and defined this human fate: romanticism. No matter what the crisis, literature places an artist in the foreground and portrays him as a protagonist who utilizes his emotions and Dionysian nature in the fight against society. Numerous protagonists are, however, doomed to either physicalor mental decay in the same fashion as the human nature is predisposed to decadent (self)-destruction.
Keywords: German-language literature; nemška književnost; Romanticism; romantika; 19. st.; 20. st.